Design of Supply Chain Management in Kasongan Pottery MSMEs - Gugum Gumilang Nurcahya; Setia Wardani; Rianto Rianto (Journal of Intelligent Software Systems, 2023)
Post-COVID 19 pandemic raises new challenges for Kasongan Bantul Pottery Micro, Small and Medium Enterprises (MSMEs), in addition to significantly changing the economic landscape, MSMEs experience challenges in marketing systems that are not yet optimal and increasingly fierce product competition is a serious obstacle. This is one of the challenges for Kasongan Pottery MSMEs so that the businesses built can succeed and be able to survive, one of which is to use a system that integrates the needs of business actors, consumers (costumers), capital owners, raw material suppliers (suppliers) and collectors without space limits. The purpose of this research focuses on the Supply Chain Management (SCM) model to improve efficiency in the supply chain of Kasongan Pottery MSMEs. The research method used is qualitative with a descriptive analysis approach. The population in this study was 303 Kasongan Pottery MSMEs, while the sample taken was 25% of the population, namely 76 MSMEs.